[CrIII8MII6]12+ Coordination Cubes (MII=Cu, Co)1. (20th April 2015) - Sanz, Sergio; O'Connor, Helen M.; Pineda, Eufemio Moreno; Pedersen, Kasper S.; Nichol, Gary S.; Mønsted, Ole; Weihe, Høgni; Piligkos, Stergios; McInnes, Eric J. L.; Lusby, Paul J.; Brechin, Euan K.
Abstract: [Cr III 8 M II 6 ] 12+ (M II =Cu, Co) coordination cubes were constructed from a simple [Cr III L3 ] metalloligand and a "naked" M II salt. The flexibility in the design proffers the potential to tune the physical properties, as all the constituent parts of the cage can be changed without structural alteration. Computational techniques (known in theoretical nuclear physics as statistical spectroscopy) in tandem with EPR spectroscopy are used to interpret the magnetic behavior.